Study on thermal performance of casing‐type mine heat recovery device with phase change materials filling in annular space. (1st August 2021) - Zhang, Xiaoyan; Xu, Muyan; Liu, Lang; Yang, Qixing; Song, KI‐IL
Summary: The underground mine contains abundant geothermal energy resources. The casing‐type mine heat recovery device with encapsulated phase change material (PCM) embedded in the backfill body is efficient technology for extraction of geothermal energy in mines. A heat transfer model of a casing‐type mine heat recovery unit was established to study the influence of PCMs thermophysical property and phase transition process on the thermal performance of backfill body. The effects of phase transition temperature, thermal conductivity, specific heat capacity and phase transition latent heat of PCMs on the temperature variation in backfill body and the thermal performance of casing‐type mine heat recovery device were studied in the heat storage/release mode. The result indicates that the phase transition temperature is expected to be lower in heat storage mode and higher in heat release mode, respectively. The heat transfer rate can be significantly enhanced by PCMs with larger thermal conductivity in both heat storage and heat release modes. Furthermore, PCMs with large specific heat capacity and latent heat should be used to improve the energy storage effect. After 10 hours of heat storage/release, when the specific heat capacity increases from 1000 to 3000 J/(kg ∙ K), the heat storage capacity and heat extraction capacity increased by 9.11% and 6.69%, respectively; when the phase transition latent heat increases from 100 to 200 kJ/Kg, the heat storage capacity and heat extraction capacity increased by 4.79% and 3.29%, respectively. Abstract : Thermal performance of casing‐type mine heat recovery device using PCM is studied. T m is expected to be lower/higher in the heat storage/release mode. Heat transfer rate can be significantly enhanced by backfilling PCM with larger λ . PCMs with greater C p and L should be used to improve the energy storage effect.